Investigating the relative contribution of colloidal and soluble fractions of secondary effluent organic matter to the irreversible fouling of MF and UF hollow fibre membranes - Filloux, E.; Gernjak, W.; Gallard, H.; Croue, Jean-Philippe (Pergamon Press, 2016)
Effluent organic matter (EfOM) matrices were modified by applying physical chemical treatments on biologically treated wastewater effluents in order to identify the EfOM fraction(s) responsible for irreversible fouling of low-pressure membranes. Anion exchange resin (AER) adsorption preferentially removed humic-like structures, while oxidation processes, such as ozonation and H2O2/UV resulted in the breakdown of high molecular weight (MW) structures into lower MW compounds. After re-concentration to the original organic carbon content, the fouling potential of the modified EfOM matrix was investigated using multi-cycle filtration tests performed with commercially available microfiltration (MF) and ultrafiltration (UF) membranes. The pre-oxidized effluents showed low fouling potential regardless of the membrane used. The results confirmed the major role of high MW biopolymers on MF and UF total fouling. Results from MF experiments highlighted that AER treated effluents exhibited similar fouling properties as the untreated effluent indicating that humic-like substances do not significantly affect MF fouling and confirm again that biopolymers is the fraction responsible for fouling. The same tests performed with UF membrane showed a lower irreversible fouling with AER treated effluent suggesting the strong contribution of humic fractions to irreversible fouling. These findings were supported by the results obtained with two different secondary effluent matrices, a conventional activated sludge treated effluent and a membrane bioreactor supernatant.